Clinical evaluation and proteomic profiles of acute myeloid leukemia patients, Saudi Arabia - Almaiman, Amer Abdulrahman (2015)
Acute myeloid leukemia (AML) represents a group of clonal hematopoietic stem cell disorders which fail to differentiate and proliferate result in the accumulation of nonfunctional myeloblasts. In AML, response of patients to therapy is variables and there is no reliable marker to predict treatment response or prognosis of the disease. In this study, the main objective was to determine proteomic profiles of AML in patients referred to the King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia. The AML patients were categorized according to risk degree based on the probability of survival. Clinical data were collected from 22 patients (16 males and 6 females) with consent. A clinical data form was developed to collect information on the diagnosis, prevention, and follow-up monitoring of AML patients. The clinical data showed that most patients (14) were cytogenetically and genetically normal and classified under the intermediate-risk category. Six patients expressed complex CCAAT/enhancer binding protein (CEBPA), FMS-related tyrosine kinase (FLT), isocitrate dehydrogenase (IDH) and Wilms tumor 1 (WT1) gene abnormalities, 2 patients showed inversion at chromosome 16 (inv.16) and 1 had t(15:17) chromosomal translocation. The high abundance protein in the samples must be depleted before subjecting to proteomic analyses. In the current study, the Pierce Albumin and IgG Removal, Albumin Depletion, and ProteoPrep® Immunoaffinity Albumin and IgG Depletion Kits were compared in the optimization of the samples. The Pierce Albumin and IgG Removal Kit was found to be the best depletion method for high abundance proteins. The protein expressions were compared among patients with different risk categories, at diagnosis and after remission. The AML samples from peripheral blood and bone marrow were analyzed by liquid chromatography tandem mass spectrometry (LCMS/MS). At diagnosis, in both the peripheral blood and bone marrow samples, 21 proteins were significantly (P<0.05) different in differential expressions among groups. The total number of proteins detected in peripheral blood was similar to those detected in bone marrow. However, there were differences in proteomic profiles between samples collected at diagnosis and remission. Most differentially expressed proteins were down-regulated in peripheral blood at remission. Among the AML cases in this study, 144 differentially expressed proteins were identified, and differences in their expression levels correlated with AML risk categories. The study showed that amphiregulin precursor (AR) (colorectum cell-derived) was expressed in low-risk AML patients only, while haptoglobin α and β and cytoplasmic tyrosyl-tRNA synthetase (EC 6.1.1.1) were highly expressed in intermediate-risk AML patients only. Lysine-arginine-ornithine-binding periplasmic protein (LAO) was expressed in intermediate and high-risk and not in the low-risk AML patients. In conclusion, the study showed that complete clinical data are essential for the determination of correlation between proteomic profile, risk categories and prediction of response to chemotherapy in AML patients. AR , haptoglobin α and β and LAO may serve as potential biomarkers for the determination of risk categories and responsiveness of AML patients to chemotherapy.